The Impact of a Pedagogical, Classroom-based Motivational Intervention on EFL Learners’ Reading Achievement - Naser Salehi; Fazlolah Samimi; Seyyed Ayatollah Razmjoo (International Journal of English Language and Translation Studies, 2018)
The present study is an attempt to investigate the effect of a type of motivational strategy designed to boost EFL learners' motivation on their reading comprehension ability. To achieve this goal, 69 EFL learners studying English in two intact classes were divided into two groups. The control group received the traditional method of pre-reading, reading, and post-reading activities while the experimental group was asked to write compositions about the factors that motivate people to learn English and read them in the class before starting their usual classroom activities. This intervention was supposed to enhance their motivation leading to better performance on reading comprehension. Then, two paired-samples t-test were run to compare the scores of both groups on the pre- and post-tests. The results of the tests showed a significant increase in the mean scores of the experimental group whereas for the control group mean scores did not change dramatically. The results of these statistical tests confirmed the efficiency of our proposed strategy in improving the learners‟ reading comprehension ability.